2012
DOI: 10.1016/s1477-3880(15)30014-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Malaysian and Singaporean Economics Undergraduates’ Academic Performance

Abstract: An international journal that promotes research into effective learning and teaching practice in economics higher educationThe International Review of Economics Education is dedicated to enhancing learning and teaching in the higher education economics community. It provides a forum for high quality research in the areas of curriculum design, pedagogy, assessment, innovation and evaluation. The journal seeks to promote critical dialogue on educational theory and practice in economics and to demonstrate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The effect of age is least pronounced for self-funded students and the same for NSFAS-and students funded by other sources. Although some studies (Mlambo, 2011;Sothan, 2019), found the age of a student does not influence academic performance, or that older students perform slightly better (Clifton 1997;Richardson, 1994), in this study the results are in line with more recent contributions that suggest that younger students perform on average better than older students (Alhajraf & Alasfour, 2014;Da Wan & Cheo 2012;Nyikahadzoi et al, 2013).…”
Section: Agesupporting
confidence: 88%
“…The effect of age is least pronounced for self-funded students and the same for NSFAS-and students funded by other sources. Although some studies (Mlambo, 2011;Sothan, 2019), found the age of a student does not influence academic performance, or that older students perform slightly better (Clifton 1997;Richardson, 1994), in this study the results are in line with more recent contributions that suggest that younger students perform on average better than older students (Alhajraf & Alasfour, 2014;Da Wan & Cheo 2012;Nyikahadzoi et al, 2013).…”
Section: Agesupporting
confidence: 88%
“…In our study, we use students’ high school averages to represent their overall academic ability. These averages are known to be good predictors of first‐year university performance and are often used as measures of students’ overall academic abilities (e.g., Arnold & Straten, 2012; Armstrong & Biktimirov, 2013; Da Wan & Cheo, 2012). We consequently expect students’ academic ability, as represented by their high school averages, to moderate the four relationships described above.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies, determinants have been investigated of how economics students" perform in end-of-term examinations (e.g., Ballard & Johnson, 2004;Buckridge & Guest, 2007;Arnold & Straten, 2012;Da Wan & Cheo, 2012) and in standardized tests of economic knowledge (e.g., Gill & Gratton-Lavoie, 2011;Hwang, 2013;Denny, 2014;Happ, Förster, Zlatkin-Troitschanskaia & Carstensen, 2016a). However, relatively little seems to be known about how students" understanding of economics develops over the course of their studies and what the determinants of this development are.…”
Section: Introductionmentioning
confidence: 99%